Co-gasification of refuse-derived fuels and bituminous coal with oxygen/steam blend to hydrogen rich gas. (1st September 2022) - Smoliński, Adam; Wojtacha-Rychter, Karolina; Król, Magdalena; Magdziarczyk, Małgorzata; Polański, Jarosław; Howaniec, Natalia
Abstract: The gasification technology of refuse-derived fuels (RDF) can represent a future alternative to the global hydrogen production and a pathway for the development of the circular economy. The paper presents an innovative way of utilizing RDF through their oxygen/steam co-gasification with bituminous coal to hydrogen rich gas. Five different RDF samples (RDF1÷RDF5) were investigated. The in-depth analyses of the co-gasification of bituminous coal blends with different amounts of RDF (10, 15 and 20%w/w) under various temperature conditions were conducted with the application of Hierarchical Clustering Analysis (HCA). The results of the research study revealed a decrease in the total gas yield as well as in the hydrogen yield observed with the increase in the RDF fraction in the fuel blend. The lowest hydrogen yield and the highest carbon conversion were noted for the co-gasification tests of coal blends with 20%w/w for all the studied RDFs. The SEM-EDS (Scanning Electron Microscopy with Energy Dispersive Spectroscopy) and WDXRF (Wavelength Dispersive X-ray Fluorescence) results showed a significantly higher H2 yield in RDF2 co-gasification with coal in comparison with all the remaining RDFs, due to the higher concentration of calcium in the sample. The molecular structure analysis of polymers using Fourier transform infrared spectroscopy (FTIR) demonstrated that the most prevalent synthetic polymers in RDF2 are polyethylene terephthalate and polyvinyl chloride characterized by the lowest thermal stability compared to polyethylene and polypropylene. Highlights: Experimental on co-gasification of coal with various refuse-derived fuel is investigated. HCA allows investigating the effect of fuel blend composition on the H2 -rich gas production. The SEM-EDS, EDXRF and FTIR results indicated the differences in the properties of the RDFs tested.